Elementary school teachers knowledge and attitude towards attention deficit-hyperactivity disorder in Gondar, Ethiopia: a multi-institutional study - Mekdes Dessie; Masresha Asmare Techane; Bizuneh Tesfaye; Daniel Ayelegne Gebeyehu (BMC, 2021)
Abstract Background A child suffering from attention deficit hyperactivity disorder (ADHD) faces many difficulties in social as well as academic performances. School teachers' knowledge and attitude towards ADHD play a vital role in early detection and referral of the child to treatment centers. Few existing reports, however, indicate the alarming rate at which the problem is highly neglected in sub-Saharan Africa. The present study is designed to determine the knowledge, attitude, and factors that affecting elementary school teachers about ADHD. Methods An institutional-based cross-sectional study design was conducted in Gondar town and other towns nearby Gondar from February 24 to March 24, 2020. Data were collected through structured self -administered questionnaires using the Knowledge of Attention Deficit Disorders Scale and ADHD-specific attitudes measurement tools. Then, it was entered into Epi-info version 7 and exported to SPSS version 20 for analysis. Bivariable and multivariate logistic regressions were fitted to identify factors associated with the knowledge and attitude of elementary school teachers. Variables having a p-value < 0.05 at 95% CI were considered statistically significant. Result Of 636 respondents, about 44.8% (95% CI 41.2, 48.4) and 84.1% (95% CI 81.0, 86.8) of elementary school teachers had good knowledge and a favorable attitude towards ADHD, respectively. Having a diploma and above (AOR = 3.028, 95% CI 1.630-5.625), reading ADHD leaflets (AOR = 2.035, 95% CI 1.391, 2.950) and search ADHD on the internet (AOR = 1.793, 95% CI 1.090, 2.950) were significantly associated with teachers knowledge to ADHD; whereas, working experience in teaching a child with ADHD (AOR = 1.852, 95% CI 1.195-2.87) and watching ADHD on mass media (AOR = 1.72, 95% CI 1.056-2.8) were positively predicts teachers attitude towards ADHD. Conclusion the proportion of teachers' knowledge towards ADHD was low; in contrast, their attitude was relatively satisfactory. Strengthening teachers' educational upgrading system, frequent and fair distribution of leaflets written to address ADHD, installation of an internet system to the schools, and continuous ADHD awareness creation programs through mass media are highly recommended.